2019
DOI: 10.1159/000500689
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Anti-Müllerian Hormone in Hypothalamic-Pituitary Function

Abstract: Since its initial discovery in the 1940s, research into the physiological actions of anti-Müllerian hormone (AMH), from its eponymous role in male developmental biology to its routine clinical use in female reproductive health, has undergone a paradigm shifting change. With several exciting studies recently reporting hitherto unforeseen AMH actions at all levels in the hypogonadal-pituitary-gonadal axis, the importance of this hormone for both hypothalamic and pituitary reproductive control is finding increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 123 publications
1
39
0
5
Order By: Relevance
“…Most notably, women with endometriosis exhibit, relative to controls: (1) shorter AGDs, indicative of lower prenatal testosterone [ 40 , 41 ], (2) lower LH relative to FSH, (3) higher SHBG, (4) higher serum oxytocin, (5) lower ovarian and serum testosterone, (6) lower AMH, (7) lower WHR and BMI, (8) lower β-endorphin and (9) a suite of other differences, all of which are opposite to the differences found between PCOS versus controls [ 3 ]. The patterns of differences between women with PCOS and endometriosis are highly concordant with one another: for example, in women without PCOS or endometriosis, higher postnatal serum testosterone has been associated with lower SHBG, longer AGD, higher LH, lower FSH, higher β-endorphin and higher WHR (e.g., [ 3 , 42 , 43 ]).…”
Section: Ontogenymentioning
confidence: 84%
“…Most notably, women with endometriosis exhibit, relative to controls: (1) shorter AGDs, indicative of lower prenatal testosterone [ 40 , 41 ], (2) lower LH relative to FSH, (3) higher SHBG, (4) higher serum oxytocin, (5) lower ovarian and serum testosterone, (6) lower AMH, (7) lower WHR and BMI, (8) lower β-endorphin and (9) a suite of other differences, all of which are opposite to the differences found between PCOS versus controls [ 3 ]. The patterns of differences between women with PCOS and endometriosis are highly concordant with one another: for example, in women without PCOS or endometriosis, higher postnatal serum testosterone has been associated with lower SHBG, longer AGD, higher LH, lower FSH, higher β-endorphin and higher WHR (e.g., [ 3 , 42 , 43 ]).…”
Section: Ontogenymentioning
confidence: 84%
“…The physiological role of AMH and its receptor in post-natal life and, particularly, from birth to puberty, is currently unknown. The presence of AMHR2 outside the gonads, and, particularly, in gonadotropic cells of the anterior pituitary gland and the hypothalamus, suggests a role for AMH as a neuroendocrine regulation of the hypothalamic-pituitary-gonadal function [ 25 ]. Interestingly, clinical evidence indicates that AMH serum levels may help in differentiating the patients with HH from those with delayed puberty in childhood [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of several in vitro and in vivo experiments showed that AMH increased the pulsatile secretion of GnRH-dependent LH through a central action. Indeed, electrophysiological experiments have revealed that exogenous AMH increased the neuronal activity of GnRH neurons; however, this could be an indirect action, as AMHR2 is very widely expressed in the hypothalamic regions, so a synergistic action of other cell types contributing to the increase in GnRH secretion cannot be excluded [for review see ( 59 )]. Similarly, the authors demonstrated that in vivo administration of AMH (intracerebroventricularly) was accompanied by a dose-dependent increase in LH secretion and pulsatility.…”
Section: Role Of Amh In the Gonadotropin Dysregulation Of Pcosmentioning
confidence: 99%